Potensi Minyak Atsiri Kayu Manis dan Kayu Lawang Sebagai Pengendali Hayati Fusarium oxysporum - Hariroh, Siti Harir; Marzuki, Ilyas; Leiwakabessy, Christoffol; Talahaturuson, Abraham (JURNAL PERTANIAN KEPULAUAN, 2025)
This research aims to analyze the potential of essential compounds of Cinnamonum burmannii and Cinnamonum cullilawan as a bioagent for Fusarium oxysporum and to test the efficacy of both essential oils in controlling the growth of the fungus F. oxysporum. Oil extraction was carried out using the steam-water distillation method, and analysis of the components of the oil compounds of the cinnamon was carried out using the GC-MS method. Essential oils were tested for their efficacy for inhibiting F. oxysporum with four concentrations, namely 0.06%, 0.125%, 0.25%, and 0.5% on PDA and PDB media. The results show that the main essential compound in C. burmannii is cinnamaldehyde at 20.61%, and in C. cullilawan, it is eugenol at 26.33%. The essential compounds of both have antifungal activity against F. oxysporum, with a concentration rate of 0.125% being able to inhibit the growth of F. oxysporum. The main active compounds, such as cinnamaldehyde and eugenol, play an important role in the fungus control mechanism. This research concludes that the essential compounds from both have the potential to inhibit F. oxysporum growth.